Organizational Readiness for AI Adoption in Indonesian Manufacturing SMEs - Maharani, Rizka (Omnia Tempus, 2023)
This study aims to explore and analyze the organizational readiness of Indonesian manufacturing Small and Medium-sized Enterprises (SMEs) in adopting Artificial Intelligence (AI) technologies. Given the pivotal role of SMEs in the national economy and their increasing exposure to digital transformation pressures, understanding their internal preparedness to integrate AI is both timely and essential. Employing a qualitative research methodology grounded in an extensive literature-based analysis, the study synthesizes empirical and conceptual findings from 45 peer-reviewed sources published between 2010 and 2024. The research adopts an interpretivist epistemological stance and applies thematic content analysis to uncover recurring patterns related to AI readiness across strategic, infrastructural, human, and institutional domains. The findings reveal that Indonesian manufacturing SMEs exhibit uneven levels of AI readiness, with significant gaps in strategic alignment, digital infrastructure, human capital development, and leadership commitment. Notably, cultural resistance and limited access to ecosystemic support further hinder sustainable AI adoption. However, the study also identifies emerging examples of collaborative innovation, particularly among SMEs engaged with universities, tech providers, and government initiatives. These cases illustrate the potential of context-sensitive readiness strategies tailored to Indonesia’s industrial landscape. The research contributes to the literature by integrating AI adoption frameworks with a nuanced understanding of local SME dynamics and offers actionable insights for business leaders and policymakers. Ultimately, this study calls for a multidimensional, continuous, and ecosystem-driven approach to AI readiness to ensure inclusive and sustainable digital transformation within Indonesia’s manufacturing sector.